Traditional Courtyard Planning for Sustainable Architecture Solutions - Sherwani, Rummana; Aslam, Seemin; Waheed, Abdul (Annals of Human and Social Sciences, 2024)
Throughout history, courtyards have played a crucial role in architectural design, offering a blend of environmental, social, and therapeutic benefits. Originating from arid and warm regions, courtyard forms have adapted globally to diverse climates and cultural contexts. This study delves into the evolution of courtyard design in Lahore, Pakistan—a city steeped in cultural heritage influenced by various civilizations. By analyzing literature, conducting observational surveys, and examining case studies, the research explores courtyard typologies, functions, design variations, and orientation patterns. Notably, rectangular courtyards prevail in Lahore, strategically oriented to maximize sunlight and ventilation. These multifaceted spaces serve as gardens, light sources, ventilation systems, playgrounds, and social hubs. The findings underscore the significance of considering climatic factors, socio-cultural influences, and user requirements in contemporary courtyard design. Architects are encouraged to create sustainable, contextually responsive designs that blend traditional wisdom with modern innovations.